Maximizing the Contribution of Fish to Human Nutrition in Assam under Assam Agribusiness and Rural Transformation Project (APART) - Ratha, Baishnaba C. (WorldFish, 2022)
Presentation for the State Level Workshop organised by Department of Fisheries, Government of Assam.